2017
DOI: 10.1042/bsr20170327
|View full text |Cite
|
Sign up to set email alerts
|

miR-214 promotes radioresistance in human ovarian cancer cells by targeting PETN

Abstract: Correspondence: Shuxiang Zhang (zhang sx19@163.com) Ovarian cancer is one of the leading causes of death among gynecological malignancies. Increasing evidence indicate that dysregulation of microRNAs (miRNAs) plays an important role in tumor radioresistance. The aim of the present study is to investigate whether microRNA-214 (miR-214) was involved in radioresistance of human ovarian cancer. Here, we showed that miR-214 was significantly up-regulated in ovarian cancer tissues and radioresistance ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
(45 reference statements)
2
26
0
Order By: Relevance
“…Several studies have demonstrated that miRNAs are involved in regulating various biological processes, including cell proliferation ( 11 ), migration ( 10 ), invasion ( 10 , 12 ) and drug resistance ( 13 ). miR-214, one member of the miR-214 family, has been revealed to be aberrantly expressed in several human cancer types, including breast cancer ( 14 ), hepatocellular carcinoma ( 15 ), lung cancer ( 13 ), esophageal squamous cell cancer ( 16 ) and ovarian cancer ( 17 ). The dysregulation of miR-214 predicts a poor prognosis in the aforementioned cancers ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that miRNAs are involved in regulating various biological processes, including cell proliferation ( 11 ), migration ( 10 ), invasion ( 10 , 12 ) and drug resistance ( 13 ). miR-214, one member of the miR-214 family, has been revealed to be aberrantly expressed in several human cancer types, including breast cancer ( 14 ), hepatocellular carcinoma ( 15 ), lung cancer ( 13 ), esophageal squamous cell cancer ( 16 ) and ovarian cancer ( 17 ). The dysregulation of miR-214 predicts a poor prognosis in the aforementioned cancers ( 13 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [18] and Li et al [19] also found miR-214 acts as a tumor suppressor in liver cancer proliferation and cell cycle. There also some different view, many researchers showed miR-214 promoted tumor pathogenesis, such as in gastric cancer cell [20, 21], ovarian cancer cells [22]. However, the roles of miR-214-5p on HCC invasion remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-668 overexpression decreases the IκBα level, increases NF-κB, and then enhances radioresistance in BC cell lines [182]. Besides, in OC, IR upregulates the expression of miR-214 in vitro and in vivo, which depresses PETN and consequently activates the PI3K/Akt pathway, resulting in radioresistance [183]. Taken together, these studies provide fresh insight into the contribution of miRNAs in multiple cancers radiation resistance, and it is essential to identify more miRNAs that can be potential therapeutic targets for radioresistant cancer patients.…”
Section: Other Cancersmentioning
confidence: 99%
“…Radiotherapy is an essential approach for locally advanced CC. However, around 30% of radiotherapy- Lung cancer miR -198 Inhibiting HGF/c-MET pathway [170] miR-99a Binding to mTOR [171] miR-558 Associating with AATK [172] miR-148b Modulating MutL homologue 1 [173] miR-335 Reducing the expression of PARP-1, downregulating NF-κB [ 174] miR-1246 Inhibiting DR5 [175] miR-21 Upregulating HIF-1α [176] miR-208a Targeting p21 with a corresponding activation of the Akt/mTOR pathway [177] Oral cancer stem cells miR-218 Activating miR-218/Bmi1 axis [178] Hepatocellular carcinoma miR-92b Reducing p57kip2 expression [179] Breast cancer miR-142-3p Attenuating CSCs characteristics and inhibiting β-catenin expression [180] miR-22 Negatively modulating Sirt1 [181] miR-668 Forming miR-668/ IκBα/NF-κB axis [182] Ovarian cancer miR-214 Depressing PETN and consequently activating PI3K/Akt pathway [183] treated patients have been found occurring recurrence or even metastasis, partially resulting from radioresistance. It has been reported that miRNAs participate in either radiation responsiveness or radioresistance.…”
Section: CCmentioning
confidence: 99%